The Conservation of Cultural Landscapes - Agnoletti, Mauro (CABI, 2014)
Cultural landscapes are today a resource whose preservation represents a most modern theme, relevant to a great number of sectors such as planning, cultural heritage preservation, rural development, nature conservation and forestry, to cite just a few. The role of the landscape and therefore its perception has changed through time; it is no longer just a ‘cultural’ aspect, intended as an elitist phenomenon, isolated from the socio-economic aspect, but emerges as an essential element in the interpretation of a modern approach to sustainable development, far from paradigmatic views, but close to the needs of a large part of society in the whole world